Hospitality Industry Employees’ Intention to Stay in Their Job after the COVID-19 Pandemic - Chien-Liang Chen; Mei-Hui Chen (Administrative Sciences, 2021)
The COVID-19 pandemic had a devastating effect on the tourism and hospitality industries in Taiwan, causing some small companies to cease trading and large companies to place their employees on unpaid leave. Placing employees on unpaid leave may have negatively affected the intention of hospitality employees to remain in their jobs. This study examined whether employees’ job insecurity and organizational identification affected their intention to stay in their job during the COVID-19 pandemic. Previously developed scales were adopted to develop items measuring job insecurity, organizational identification, and intention to stay in a job. Responses to 515 returned questionnaires were examined. The results revealed that job insecurity significantly affects organizational identification. Both job insecurity and organizational identification significantly affected intention to stay. Few studies have used path analyses to investigate the relationships among intention to stay, job insecurity, and organizational identification. The indirect effect of organizational identification was analyzed, and evidence supporting a total effect and total indirect effect was obtained. This implies that hospitality companies seeking to retain staff during crises should promote organizational identification among staff.